Do Renal Cysts Affect the Success of Extracorporeal Shockwave Lithotripsy? A Retrospective Comparative Study - Adnan Gücük; Ufuk Öztürk; Uğur Üyetürk; Eray Kemahlı; Güven Akın; M. Abdurrahim İmamoğlu; Ahmet Metin (Advances in Urology)
The aim of this study was to assess the effect of simple renal cysts on extracorporeal shockwave lithotripsy (SWL) in patients with calyceal renal calculi. Patients with simple renal cysts >35 mm and ipsilateral renal calculi <20 mm that were treated with SWL constituted group 1 (cyst + calculi). The control group included patients aged >40 years that had renal calculi <20 mm and no cysts that were treated with SWL. The 2 groups were compared according to age, gender, body mass index, calculi size, localization, and density, the calculi fragmentation rate, and the percentage of stone-free patients. Mean cyst size in group 1 was 44.04±9.08 mm. Mean age in group 1 was 61.4±10.2 years versus 56.9±8.2 years in the control group; the difference was significant (P=0.045). There were not any other significant differences between the 2 groups, except for the stone-free rate (P>0.05), which was 33.3% in group 1 and 68.2% in the control group (P=0.017). The presence of renal cysts in a patient with calculi requires that an individualized treatment plan be devised, so as to provide the patient with the most effective treatment.